1980
DOI: 10.1001/archderm.116.4.448
|View full text |Cite
|
Sign up to set email alerts
|

Triangular lunulae. A clue to nail-patella syndrome

Abstract: The nail-patella syndrome has been of interest to dermatologists because the diagnosis of this multisystem complex may be suggested simply by observing the patient's abnormal nails. It is the purpose of this article to call attention to triangular lunulae and other nail abnormalities associated with this syndrome, as well as other causes of triangular lunulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Absence of thumb nails and patellae with osseous dysplasia is known as the nail-patella syndrome. Many nail changes have been described in this condition, including anonychia, koilonychia, and pterygium; nonspecific cracking and splitting are probably the most common findings, A triangular lunula, if present, is highly suggestive of this condition (10), The toenails also may be affected (in,…”
Section: Anonychiamentioning
confidence: 99%
“…Absence of thumb nails and patellae with osseous dysplasia is known as the nail-patella syndrome. Many nail changes have been described in this condition, including anonychia, koilonychia, and pterygium; nonspecific cracking and splitting are probably the most common findings, A triangular lunula, if present, is highly suggestive of this condition (10), The toenails also may be affected (in,…”
Section: Anonychiamentioning
confidence: 99%
“…In a retrospective study of 123 cases of NPS reported in the literature by Meyrier et al, 60% of patients presented with non-nephrotic range proteinuria. The proteinuria may remain asymptomatic, remit spontaneously, or may progress to nephrotic syndrome in less than 20% of the patients [8,10,11]. In this study, 15% of the patients progressed to ESRD.…”
Section: Discussionmentioning
confidence: 64%
“…NPS is a rare autosomal dominant disorder characterized by a broad spectrum of clinical manifestations with variable presentation 2‐5 . The “classic” tetrad includes patellar or elbows dysplasia, presence of iliac horns and nail dystrophy 2,3 .…”
Section: Discussionmentioning
confidence: 99%